SYNERGITY BETWEEN THE VILLAGE GOVERNMENT AND PADJADJARAN UNIVERSITY IN ENCOURAGING THE DEVELOPMENT OF COMMUNITY ENTREPRENEURS IN JATIMUKTI VILLAGE - Djuyandi, Yusa; Pradana, Aditya; Luqman, Fahmy (International Journal of Management, Innovation & Entrepreneurial Research, 2020)
Objective: This study is aimed to examine the development of entrepreneurship to improve welfare in Jatimukti village, Sumedang Regency, is one form of activity in the economic field by empowering rural communities. Efforts to encourage the development of entrepreneurship in the village can be done by synergizing the existence and role of the stakeholders, including the village government with universities. Methodology: In the research process, the method used is qualitative, where data research is obtained from interviews and observations. The collected data is then classified based on its type, after that the verification and validation process is carried out through triangulation techniques. Main Findings: The results of this study indicate that the synergy between institutions in encouraging the development of entrepreneurship in Jatimukti village community, especially between the village government and universities, is important. Implications: In its implementation, the Padjadjaran University with the Government of Jatimukti Village has conducted a synergy with a series of activities and coordination to advance community entrepreneurship. Novelty/Originality of the Study: To achieve good results from the synergy process, effective communication, fast feedback, trust and creativity are needed. The value of such relationships, such as loyalty to partners, maintaining interdependence, adaptation to partners (cultural compatibility), integrity and intensity of relationships, and institutionalization (means acting on behalf of institutions and in the interests of shared institutions).